PERANCANGAN SISTEM INFORMASI GEOGRAFIS (SIG) SEBAGAI MEDIA INFORMASI PRAKERIN BERBASIS WEB DI SMKN 6 TANGERANG SELATAN - Chaidir Kurnia Thoullah; Agnia Bilqisti; Dhimas Alifiyanto (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2019)
Industry Work Practice or commonly called the PRAKERIN is an activity that must be followed by every vocational students during school as a form of implementation of science or as an addition to an insight into the working world they will face in the future . But obstacles that was often faced by student is in the search company locations the industrial work practice . From the problem, we need to make a web based geographic information system (GIS) that provides information about the location of company in Tangerang. In search of the location or place, it would require a geographic information. Nowadays, people mostly use Google Maps application. To overcome the obstacles mentioned above, the authors usea SWOT (Strength, Weakness, Opportunity, Thread) to identify the obstacles encountered in greater detail.To create a model or design of an expert system, the authors use UML (Unified Modeling Language) as a tools. and taking data sources form map's that author got from Google Maps API,location’s data sources form SMKN 6 Tangerang selatan that has been cooperated with the company. The author hopes the student can easyly access the location place the industrial work practice .